Qualitative analysis and exploration of anti-inflammatory and antibacterial effects of a Thai traditional medicine formula from Wat Pho beyond its use for COVID-19 treatment - Naruemon Perstwong; Asma Binalee; Khwanlada Kobtrakul; Wongsakorn Phongsopitanun; Kittipong Sanookpan; Sudartip Areecheewakul; Visarut Buranasudja; Sornkanok Vimolmangkang (BMC Complementary Medicine and Therapies)
Abstract Background Ya-Kao (YK) is a traditional Thai medicine used to relieve fever and consists of 14 crude drugs. It has been recommended by Thai folk healers and the Department of Thai Traditional and Alternative Medicine for COVID-19 treatment, with clinical studies conducted to assess its efficacy. However, scientific evidence on its biological properties remains limited. This study aims to explore the quality aspect of YK and evaluate its antibacterial and anti-inflammatory effects. Methods The quality aspect of the YK formula was assessed using high-performance thin-layer chromatography (HPTLC). Agar disc diffusion and TLC bioautography were used for antibacterial activity, while anti-inflammatory effects were evaluated by measuring nitric oxide (NO) production in LPS-stimulated RAW264.7 macrophages. Results The HPTLC method, utilizing a developing system of toluene, ethyl acetate, and formic acid (70:30:1, v/v/v), was successfully developed for the authentication of YK crude drugs. This method provides the most distinct fingerprint pattern of the components within the YK formulation, enabling clear visualization of its constituent. Additionally, it enables preliminary identification of phenolics, terpenes, and steroids, providing valuable insight into the formulation’s chemical composition. The antibacterial activity of YK was evaluated using the disk diffusion assay, and it was found that the lime juice extract of the YK formula (LYK) exhibited the largest zone of inhibition against both Gram-positive and Gram-negative bacterial strains, particularly those pathogenic to the respiratory tract. Additionally, the antibacterial activity was evaluated using TLC bioautography, and the results indicated that the methanolic extract of YK (MYK) exhibited an inhibition zone against Streptococcus pyogenes and Klebsiella pneumoniae. It was found that several compounds displayed an inhibition zone. Furthermore, the YK extract with methanol, water, and lime juice exhibited significant anti-inflammatory properties by suppressing NO accumulation in LPS-stimulated macrophage cells (p < 0.05). Conclusions This study is the first to standardize YK raw materials using HPTLC and evaluate the biological properties of each crude drug and the combined formula. The developed HPTLC method ensures accurate identification of YK raw materials, preventing the use of incorrect ingredients. Additionally, the pharmacological findings confirm YK’s anti-inflammatory and antibacterial activities, particularly against respiratory pathogens linked to COVID-19.